Optical fiber telecommunications IIIA - Kaminow, Ivan P., 1930-; Koch, Thomas L. (San Diego, CA : Academic Press, 1997)
Updated to include the latest information on light wave technology, Optical Fiber Telecommunication III, Volumes A & B are invaluable for scientists, students, and engineers in the modern telecommunications industry. This two-volume set includes the most current research available in optical fiber telecommunications, light wave technology, and photonics/optoelectronics. The authors cover important background concepts such as SONET, coding device technology, andWOM components as well as projecting the trends in telecommunications for the 21st century. Key Features * One of the hottest subjects of today's technology * Includes the most up-to-date research available in optical fiber telecommunications * Projects the trends in telecommunications for the 21st century.
Includes bibliographical references and index.
Keywords: Fiber optics; Optical communications; Electronic books